Are there differences in running economy at different velocities for well-trained distance runners? - Helgerud, J.; Støren, Ø.; Hoff, J. (European Journal of Applied Physiology, 2010)
The present study investigated whether there are differences in running economy at different velocities for well-trained distance runners, and to what extent a commonly used incremental protocol for measuring oxygen uptake (VO2) at different velocities affects the reliability of these measurements. Fifteen well-trained distance runners (9 male and 6 female) participated in this study. Gross oxygen cost of running (C R), heart rate (HR) and [La-]b during 5-min runs at velocities ranging from 8.0 to 17 km h-1, representing intensities ranging from 60 to 90% of maximal oxygen consumption (VO2max) was measured on two different days in random order. The athletes were also tested for lactate threshold, VO2max and time to exhaustion at MAS (tMAS). No significant differences in C R between the different relative velocities or the different set velocities were found up to 90% of VO2max. The incremental protocol for measuring VO2 at different velocities was found not to affect the reliability of these measurements. All athletes reached their VO2max whilst running to exhaustion at MAS. The females showed significantly lower VO2max, but significantly better C R than the males. At velocities representing intensities between 60 and 90% of VO2max, no differences in C R were found. The commonly used incremental protocol for measuring oxygen uptake (VO2) at different velocities was found not to affect the reliability of these measurements. This means that C R measured at sub-maximal velocities are representative for C R at race velocity for distances above 10,000 m for most runners.